Passive Building Design Approach in Iban Long houses - Viviellenie, Ngitar; Azhaili, Baharun; Ruzanah, Abu Bakar; Awang Hasim, Awang Sulong; Imran, Ali (IJASR, 2021)
Passive Design is design that uses the advantage of the climate for maintaining the thermal comfort inside the room. Comfort inside the house can be achieved with less dependence on artificial lighting and mechanical ventilation, and the application of eco-friendly materials. Timbers and bamboos are examples of eco-friendly materials which are excellent in lessen heat flow and with proper inlet and outlet allow natural ventilation thus giving comfort to occupants. These materials are widely used in the construction of Iban longhouses in Sarawak, Malaysia. Therefore, a study has been conducted to assess the presence of passive building design approach in the Iban longhouse in Sarawak. In the study, site observation with photo analysis, experimental work and CFD simulation by Autodesk CFD software were carried out at eight selected Iban longhouses in Sarawak. This study found that Iban longhouses practice passive building design. Iban longhouse implements passive design strategies in achieving comfort for occupants. This contributes to natural adaptation to the hot and humid weather conditions in the tropical climate. The findings are expected to generate ideas for bioclimatic building design for other modern terrace houses in a tropical climate. In conclusion, the Dayak traditional longhouse in Sarawak, Malaysia is a good example of bioclimatic building design of the past.